KERAGAAN CIRI KUANTITATIF MORFOLOGI GALUR-GALUR HARAPAN KEDELAI (Glycine max L. Merill) TAHAN CpMMV (Cowpea Mild Mottle Virus) - Setiawan, Tri Andri; Zubaidah, Siti; Kuswantoro, Heru (Bioedukasi Jurnal Pendidikan Biologi, 2016)
Morphology is performance of a genotype that is influenced by environmental and genetic interaction. This research was to study the quantitatively morphological characters of ten CpMMV-resistant soybean promising lines, i.e. UM.4-1, UM.7-2, UM.2-4, UM.7-6, UM.6-2, UM.6-3, UM.3-2, UM.6-1, UM.7-3, UM.3-4 and two superior varieties Gumitir and Wilis. The study was conducted at Indonesian Legume and Tuber Crops Research Institute (ILETRI) from March to June 2015. The observation was done by measuring the quantitative morphological characters such as leaf length, leaf width, leaf petiol length, leaf area, leaf ratio (P/L) and plant height. The data were tested using multivariate analysis. The results of the analysis showed that there were differences on morphological characters of CpMMV-resistant soybean promising lines as well as superior varieties Gumitir and Wilis based on the leaf length, leaf width, leaf petiol length, leaf area, leaf ratio (P/L) and plant height. Hotellings Trace (0.00) was smaller than the significance value (0.05) showing the differences among the groups.Kata Kunci: kedelai, CpMMV, karakter morfologi kuantitatif